1990
DOI: 10.1159/000163579
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Spermidine Uptake in Cultured Mammalian Cells and Its Inhibition by Some Polyamine Analogues

Abstract: Transport pathways for spermidine (Spd) were characterized in mammalian cells in culture of different origin, i.e. L 1210, P 388, C 6, U 251, Balb/c 3T3 normal and transformed by virus SV40 (SV40/3T3). The kinetic constants (Km and Vmax) for 14C-Spd uptake were found to be different in these cells. Spd uptake was inhibited by spermine and putrescine in all cells. Preloading of these cells with system A and other amino acids, including ornithine, usually did not affect Spd uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Ca 2ϩ is also known to affect polyamine transport into eukaryotes, although the effects are disparate. Ca 2ϩ stimulates polyamine uptake in human fibroblasts (48) and breast cancer cells (47), whereas the divalent cation inhibits polyamine transport into embryonic mesenchymal cells (49) and Neurospora crassa (50). Because the calcium ionophore A23687 inhibited putrescine uptake into TUB::HD309-LmPOT1 T. brucei, it is possible that putrescine transport via LmPOT1 is Ca 2ϩ -dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2ϩ is also known to affect polyamine transport into eukaryotes, although the effects are disparate. Ca 2ϩ stimulates polyamine uptake in human fibroblasts (48) and breast cancer cells (47), whereas the divalent cation inhibits polyamine transport into embryonic mesenchymal cells (49) and Neurospora crassa (50). Because the calcium ionophore A23687 inhibited putrescine uptake into TUB::HD309-LmPOT1 T. brucei, it is possible that putrescine transport via LmPOT1 is Ca 2ϩ -dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Since the putrescine acceptor sites were supposed to be involved in putrescine uptake (4), and could be considered as a potential target for anticancer drug design, our experiments have been carried out in order to characterize their specificity. We observed that methylation of the two primary amine functions of putrescine did not prevent recognition by the putrescine binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Values for this uptake velocity from a number of different mammalian cell lines suggest that 2-5 nmol/10 6 cells per h is a common range [7,[17][18][19]23,24]. At this velocity the spermidine or spermine level of a cell could be doubled in 1 h!…”
Section: Polyamine Transporter Velocitymentioning
confidence: 96%
“…Although there may be some cell-type variation, kinetic studies of mammalian polyamine uptake generally suggest an apparent K m of spermine for the transporter at 1 µM or less [7,[17][18][19][20]. The triamine spermidine demonstrates almost the same affinity as spermine, while putrescine is found to be a poorer substrate with an apparent K m in the 5-10 µM range.…”
Section: Transporter Affinity For Spermidine and Sperminementioning
confidence: 99%